Genetic algorithms approach for containerships fleet management dependent on cargo and their deadlines - Moura, Ana (2012)
This work proposes a method to improve the flexibility of short sea shipping and to increase its competitiveness with other means of freight transport. A logistic model and a mathematical model are developed to manage a fleet of two or more vessels which transport cargo to and from several ports, bearing in mind the cargo distribution and delivery deadlines. At each port, the model determines which port to visit next, which containers to embark, disembark and to shift, as well as how to stow them on board. In fact, this formulation brings together the fleet management problem, the container stowage problem (CSP) and the vehicle routing problem (VRP). An example scenario is set up, using generated but realistic data. The problem is then solved, in a simplified version, using a Genetic Algorithm. The results show that introducing the possibility of route changes, the overall efficiency (and thus competitiveness) of short sea shipping can be improved.